'Communicative competence' in the field of augmentative and alternative communication: a review and critique. Issue 1 (30th August 2013) - Teachman, Gail; Gibson, Barbara E.
Abstract Background Understandings of 'communicative competency' (CC) have an important influence on the ways that researchers and practitioners in augmentative and alternative communication (AAC) work toward achieving positive outcomes with AAC users. Yet, very little literature has critically examined conceptualizations of CC in AAC. Following an overview of the emergence of the concept of CC and of the field of AAC, we review seven conceptualizations of CC identified in the literature. Aims To consider the contributions and potential shortcomings of conceptualizations of CC in AAC. Methods & Procedures We use a critical theoretical approach to review, critique and synthesize conceptualizations of CC in AAC, with a particular focus on uncovering 'taken for granted' assumptions. By historically situating the reviewed literature, we examine the shifting boundaries and tensions among theoretical conceptualizations of CC in AAC and their potential impacts on practice. Main contributions We suggest ways that revisiting past scholarly work, alongside emergent, innovative conceptualizations of CC might shift ways of thinking about CC in AAC which tend to focus on the individual who communicates differently, toward (re)location of CC as a shared, socially incorporated and performed communication construct. Conclusion & Implications We propose that emerging critical perspectives drawn from AAC and other interdisciplinary literatures offer innovative ways of theorizing communication difference, which might inform evolving conceptualizations of CC in AAC.